Globalisation and global trading system: impacts on businesses / Rosiatimah Mohd Isa - Mohd Isa, Rosiatimah (2002)
Globalisation is the phenomenon of the integration of markets worldwide into a single global economy known as free market system that offers equal access to opportunity as entry barriers for trade and investment decline. The world free trading system started off with GATT under U.S leadership that later led to the formation of WTO and regional trading blocks such as NAFTA, EAEC and AFTA to name a few. AFTA is important as a medium-term vehicle allowing ASEAN countries to participate in the negotiation process towards liberalised global trading. To benefit fullest from globalisation and global trading system, the entrepreneurs have to develop appropriate strategies to maintain an edger over their competitors. In addition business operations may require adjustments and adaptation in order to survive in the new volatile business environment. This paper attempts to look at the definition of globalisation, development of liberalised global trading system and at later part reviews some of the impacts on businesses particularly in Malaysia.